A kind of garbage leachate membrane concentrate treating agent and preparation method thereof

By using a treatment agent combined with a carbon nanotube-gelan gel composite material and a hydrogen peroxide/persulfate system, the problem of difficult degradation of organic matter and heavy metals in the waste leachate membrane concentrate is solved, and efficient pollutant removal and stable treatment effect is achieved.

CN119349699BActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411926392.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

It is difficult to treat garbage leachate membrane concentrate. The existing technology has problems such as high processing costs, complex processes, and difficulty in operating and maintaining, making it difficult to effectively remove difficult-to-degrade organic matter and heavy metals.

Method used

The carbon nanotube-gelan gel composite material is combined with the hydrogen peroxide/persulfate system to form a strong oxidation system. Through the synergistic action of adsorption-oxidation, the treatment agent with multiple action mechanisms is constructed.

Benefits of technology

It significantly improves the degradation efficiency of difficult-to-degrade organic matter, improves the removal rate of heavy metals, and has better treatment effect than a single adsorption or oxidation treatment method, and improves process stability and applicability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of waste liquid treatment, and discloses a treatment agent for landfill leachate membrane concentrate and a preparation method thereof. The treatment agent for landfill leachate membrane concentrate comprises the following raw materials in parts by weight: 2 to 5 parts of carbon nanotube-gellan gum, 15 to 25 parts of hydrogen peroxide / persulfate, 8 to 12 parts of polyacrylamide, 3 to 6 parts of sodium hydroxide, 10 to 15 parts of activated carbon, and 4 to 8 parts of citric acid; wherein, carbon nanotube-gellan gum is a composite obtained by reacting carbon nanotubes and gellan gum in a mass ratio of 1: (2 to 4); hydrogen peroxide / persulfate is a composite system of hydrogen peroxide and persulfate. In the treatment agent provided by the present invention, carbon nanotubes and gellan gum are used in combination, gellan gum not only improves the dispersibility of carbon nanotubes, but also enhances the adsorption effect by its gel network, and synergizes with the remaining components, and establishes an efficient pollutant removal mechanism through adsorption-oxidation synergy, significantly improving the degradation efficiency of difficult-to-degrade organic matter, and the treatment effect is far better than a single adsorption or oxidation treatment method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste liquid treatment, and in particular to a garbage leachate membrane concentrate treating agent and a preparation method thereof. Background Art

[0002] The treatment of landfill leachate membrane concentrate has always been a difficult problem in the field of environmental protection. With the acceleration of urbanization, the output of domestic waste continues to increase, and the amount of leachate generated by landfills has also increased. These leachates contain high concentrations of organic matter, heavy metals and other pollutants. If they are discharged directly without treatment, they will cause serious pollution to the environment. At present, the treatment of landfill leachate mainly adopts the "biological + double membrane method" (nanofiltration + reverse osmosis), but this process will produce 20~30% membrane concentrate. These concentrates have complex components and are more difficult to handle, becoming one of the main treatment problems faced by landfills.

[0003] The characteristics of membrane concentrate are that it contains high concentrations of refractory organic matter, heavy metals and other pollutants, and has low biodegradability. It is difficult to effectively treat it with traditional wastewater treatment technology. Currently, the commonly used treatment methods such as recharge, advanced oxidation and evaporation can treat membrane concentrate to a certain extent, but they all have obvious limitations. Although the recharge method is simple to operate, it may increase the hardness of the landfill leachate and reduce its biodegradability. Long-term use may also cause pollutants to accumulate in the landfill, increasing the risk of groundwater pollution. Although advanced oxidation technology has a good removal effect on organic matter, it often needs to be used in conjunction with other processes to meet emission standards. In addition, the energy consumption during the treatment process is high, the operating cost is expensive, and it also faces problems such as unstable treatment effect and possible secondary pollution caused by by-products. Although the evaporation method can greatly reduce the volume of the concentrate, it still faces the problem of safe disposal of the secondary concentrate, and it has high energy consumption and large equipment investment, which is not suitable for large-scale application. In addition, these methods generally have common problems such as high treatment cost, complex process, and difficult operation and maintenance, which make it difficult to be widely used in actual engineering.

[0004] Faced with these challenges, researchers have been exploring more effective and economical treatment technologies. In recent years, some new treatment methods such as electrochemical oxidation, supercritical water oxidation, and wet oxidation have gradually attracted attention, but these technologies are still in the laboratory or small-scale test stage and are still a long way from large-scale engineering applications. Summary of the invention

[0005] The object of the present invention is to provide a landfill leachate membrane concentrate treating agent and a preparation method thereof, so as to improve the removal efficiency of refractory organic matter in landfill leachate membrane concentrate and reduce the content of heavy metals.

[0006] To achieve the above object, on the one hand, the present invention provides a landfill leachate membrane concentrate treating agent, comprising the following raw materials in parts by weight: 2 to 5 parts of carbon nanotube-gellan gum, 15 to 25 parts of hydrogen peroxide / persulfate, 8 to 12 parts of polyacrylamide, 3 to 6 parts of sodium hydroxide, 10 to 15 parts of activated carbon, and 4 to 8 parts of citric acid;

[0007] Wherein, carbon nanotube-gellan gum is a composite obtained by reacting carbon nanotube and gellan gum in a mass ratio of 1:(2-4);

[0008] Hydrogen peroxide / persulfate is a composite system of hydrogen peroxide and persulfate.

[0009] Preferably, the persulfate includes any one or more of sodium persulfate, potassium persulfate and ammonium persulfate.

[0010] Preferably, the preparation method of the carbon nanotube-gellan gum is: uniformly dispersing the pretreated multi-walled carbon nanotubes in deionized water, adding a gellan gum solution with a pH of 7 to 8, centrifuging after sufficient reaction, retaining the precipitate, washing, drying, grinding and sieving.

[0011] Preferably, the pretreatment of the multi-walled carbon nanotubes is a treatment to remove impurities and improve dispersibility.

[0012] Preferably, the raw materials also include: 5 to 10 parts of asphalt carbon fiber-kaolin.

[0013] Preferably, the pitch carbon fiber-kaolin is a composite obtained by reacting pitch carbon fiber and kaolin in a mass ratio of (1.5-2.5):1.

[0014] Preferably, the preparation method of asphalt carbon fiber-kaolin is: the pretreated kaolin is evenly mixed with the asphalt solution, and after high-temperature carbonization under a nitrogen atmosphere, it is cooled, ground, sieved, washed, and dried.

[0015] Preferably, the pretreatment of kaolin is a treatment to remove impurities and change the surface chemical properties of kaolin.

[0016] Preferably, the carbonization temperature is 600-800°C.

[0017] On the other hand, the present invention also provides a method for preparing a landfill leachate membrane concentrate treating agent, comprising mixing all raw materials uniformly, performing ultrasonic treatment, standing, suction filtering, drying, grinding and screening.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. In the treatment agent provided by the present invention, carbon nanotubes and gellan gum are used in combination. The gellan gum not only improves the dispersibility of the carbon nanotubes, but also enhances the adsorption effect through its gel network. The strong oxidation system formed by sulfate radicals and hydroxyl radicals generated by the hydrogen peroxide / persulfate system establishes an efficient pollutant removal mechanism through the adsorption-oxidation synergistic effect, significantly improves the degradation efficiency of difficult-to-degrade organic matter, and the treatment effect is far better than that of a single adsorption or oxidation treatment method.

[0020] 2. The raw material of the treatment agent of the present invention can also use asphalt carbon fiber-kaolin composite materials. The conductive properties of asphalt carbon fiber and the layered structure of kaolin complement each other, giving full play to the synergistic effect of each functional component and further enhancing the interception and removal of pollutants. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The first embodiment of the present invention provides a landfill leachate membrane concentrate treating agent, comprising the following raw materials in parts by weight: 2 to 5 parts of carbon nanotube-gellan gum, 15 to 25 parts of hydrogen peroxide / persulfate, 8 to 12 parts of polyacrylamide, 3 to 6 parts of sodium hydroxide, 10 to 15 parts of activated carbon, and 4 to 8 parts of citric acid;

[0023] Wherein, carbon nanotube-gellan gum is a composite obtained by reacting carbon nanotube and gellan gum in a mass ratio of 1:(2-4);

[0024] Hydrogen peroxide / persulfate is a composite system of hydrogen peroxide and persulfate.

[0025] The landfill leachate membrane concentrate treatment agent provided by the present invention constructs an efficient treatment system through the synergistic effect of multiple components. The system fully utilizes the unique properties of various raw materials and realizes the comprehensive treatment of pollutants through multiple action mechanisms. The details are as follows:

[0026] The carbon nanotube-gellan gum composite material is the core component of the treatment system. Carbon nanotubes, with their unique tubular structure and huge specific surface area, provide abundant adsorption sites for pollutant molecules. However, the easy aggregation of carbon nanotubes limits their practical application effect. As a natural polysaccharide, gellan gum can not only significantly improve the dispersibility of carbon nanotubes, but its unique three-dimensional network structure can also enhance the overall adsorption performance in the gel state formed in aqueous solution. This composite material not only maintains the excellent adsorption performance of carbon nanotubes, but also overcomes the disadvantage of poor dispersibility, and shows excellent removal effect on organic pollutants and heavy metal ions.

[0027] In terms of chemical oxidation degradation, the hydrogen peroxide / persulfate synergistic oxidation system plays a key role. Under appropriate conditions, persulfate can produce sulfate radicals (SO4 - •), while hydrogen peroxide can generate hydroxyl radicals (•OH). The synergistic effect of these two free radicals forms a powerful oxidative degradation system, which can effectively break the molecular structure of refractory organic matter and convert it into small molecules, or directly achieve complete mineralization, thereby reducing the organic matter content of sewage.

[0028] The addition of polyacrylamide further enhances the treatment effect. As a polymer flocculant, polyacrylamide can bridge and connect dispersed pollutant particles through its long-chain molecular structure, promote their aggregation to form larger flocs, and facilitate solid-liquid separation. At the same time, with the cooperation of sodium hydroxide, it can not only adjust the pH value of the system to the optimal range, but also promote the formation of hydroxide precipitation of metal ions, thereby significantly improving the separation efficiency of pollutants.

[0029] The introduction of activated carbon provides deep adsorption capacity for the treatment system. Its developed pore structure can not only adsorb residual pollutants in the solution, but also show excellent removal effect on color substances. More importantly, the use of activated carbon can effectively prevent secondary pollution generated during the treatment process and ensure the stability of the effluent water quality.

[0030] Citric acid plays multiple roles in this treatment system. First, as an organic acid chelating agent, it can accurately adjust the pH value of the solution through the carboxyl group in its molecule; second, the carboxyl group in the citric acid molecule can form a stable complex with metal ions to promote the removal of metal ions, and can also interact with organic pollutants through the carboxyl group to enhance the removal effect, playing a dual role of pH adjustment and pollutant complexation in the treatment process.

[0031] This treatment agent combines multiple action mechanisms such as physical adsorption, chemical oxidation, flocculation sedimentation and deep filtration. Through the complementary advantages and synergistic enhancement of each component, it not only achieves the efficient removal of complex pollutants in the membrane concentrate of landfill leachate, but also improves the stability and applicability of the treatment process, providing an innovative solution for this type of difficult-to-treat wastewater.

[0032] It should be noted that the mass ratio of carbon nanotubes to gellan gum during the preparation process is 1: (2-4). If the amount of gellan gum is insufficient, it cannot fully disperse and stabilize the carbon nanotubes, resulting in carbon nanotube agglomeration and reduced adsorption effect; if the amount of gellan gum is too much, it will reduce the specific surface area of ​​the composite and affect the adsorption performance. The best effect is achieved when the mass ratio of the two is 1:3.

[0033] For the preparation method of carbon nanotube-gellan gum, no special limitation is required, and a suitable preparation method is selected by those skilled in the art according to the characteristics of the composite raw material itself. Exemplarily, the preparation method of carbon nanotube-gellan gum is: the pretreated multi-walled carbon nanotubes are uniformly dispersed in deionized water, a gellan gum solution of pH 7~8 is added, centrifuged after sufficient reaction, the precipitate is retained, washed, dried, and ground and sieved. Among them, pretreatment of multi-walled carbon nanotubes is a commonly used process for removing impurities and improving dispersibility, and pretreatment is used to create more optimal conditions for subsequent composite material preparation. Specifically, the pretreatment method is: multi-walled carbon nanotubes are mixed with acid, and ultrasonic treatment, magnetic stirring, suction filtration, washing, and drying are processed.

[0034] In order to further enhance the removal effect of pollutants, in some preferred embodiments, the raw material of the treatment agent also contains asphalt carbon fiber-kaolin. The introduction of asphalt carbon fiber-kaolin composite materials adds a new functional dimension to the treatment system. Asphalt carbon fiber has good conductivity and chemical stability, can promote electron transfer, and enhance the efficiency of redox reactions. Kaolin can adsorb various ionic pollutants through interlayer intercalation and ion exchange, and the abundant silicon hydroxyl and aluminum hydroxyl groups on its surface can also participate in the removal process of pollutants through coordination.

[0035] For asphalt carbon fiber-kaolin, the asphalt carbon fiber and kaolin need to be mixed and reacted in a mass ratio of (1.5~2.5):1 during the preparation process. If the mass ratio of the two is less than 1.5:1, the organic matter removal effect will decrease and the mechanical strength of the composite will be insufficient; if the mass ratio of the two is greater than 2.5:1, the heavy metal removal rate will decrease and the cost will increase. When the mass ratio of the two is 2:1, the effect is best.

[0036] The preparation method of asphalt carbon fiber-kaolin is to mix the pretreated kaolin with the asphalt solution evenly, carbonize at high temperature under a nitrogen atmosphere, cool, grind, screen, wash and dry. Among them, the pretreatment of kaolin is to remove impurities, change the surface chemical properties of kaolin, increase the surface negative charge, and improve its interaction with asphalt carbon fiber. Specifically, the pretreatment method is: dry the kaolin at 100~105℃ for 4~5h, soak it in sodium hydroxide for 24~36h, filter, wash and dry.

[0037] The second aspect of the present invention discloses a method for preparing a treatment agent for landfill leachate membrane concentrate, which comprises mixing various raw materials uniformly, and then subjecting them to ultrasonic treatment, standing, suction filtering, drying, grinding and screening.

[0038] It should be noted that the preparation method of the treatment agent of the present invention is a commonly used method for preparing sewage treatment agents, that is, after the raw materials are evenly mixed, the obtained solid product is dried and ground to a suitable particle size.

[0039] In order to make the scheme of the present invention clearer, the landfill leachate membrane concentrate treatment agent and its performance are described in detail through multiple specific embodiments below.

[0040] In the following examples and comparative examples, “parts” are all “parts by weight”.

[0041] Example 1

[0042] The raw materials of the landfill leachate membrane concentrate treatment agent are: 3 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:3), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 5 parts of sodium hydroxide, 12 parts of activated carbon, and 6 parts of citric acid.

[0043] Among them, the preparation method of carbon nanotube-gellan gum is as follows: add multi-walled carbon nanotubes to mixed acid (volume ratio of sulfuric acid and nitric acid is 3:1), ultrasonically treat for 2 hours at 40°C, magnetically stir at room temperature for 12 hours, filter, wash with deionized water until neutral, and vacuum dry to obtain pretreated multi-walled carbon nanotubes; prepare a gellan gum solution with a concentration of 1-2wt% with deionized water, adjust the pH to 7-8, and cool to room temperature for use; evenly disperse the pretreated multi-walled carbon nanotubes in deionized water, slowly add the gellan gum solution, after sufficient reaction, centrifuge for 15 minutes, retain the precipitate, wash the precipitate, vacuum dry, and grind and sieve 200 mesh.

[0044] The preparation method of the landfill leachate membrane concentrate treating agent is as follows: the raw materials are mixed successively, ultrasonically treated for 30 minutes, allowed to stand for 12 hours, filtered, dried, and ground to pass through a 200-mesh sieve.

[0045] Example 2

[0046] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 2 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:3), 15 parts of hydrogen peroxide / persulfate, 8 parts of polyacrylamide, 3 parts of sodium hydroxide, 10 parts of activated carbon, and 4 parts of citric acid. The preparation method of the raw materials and the treatment agent is as shown in Example 1.

[0047] Example 3

[0048] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 5 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:3), 25 parts of hydrogen peroxide / persulfate, 12 parts of polyacrylamide, 6 parts of sodium hydroxide, 15 parts of activated carbon, and 8 parts of citric acid. The preparation method of the raw materials and the treatment agent is as shown in Example 1.

[0049] Example 4

[0050] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 3.5 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:2), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 4.5 parts of sodium hydroxide, 12.5 parts of activated carbon, and 6 parts of citric acid. The preparation method of the raw materials and the treatment agent is as shown in Example 1.

[0051] Example 5

[0052] The raw materials of the landfill leachate membrane concentrate treatment agent are: 3 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:3), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 5 parts of sodium hydroxide, 12 parts of activated carbon, 6 parts of citric acid, and 8 parts of asphalt carbon fiber-kaolin (the mass ratio of asphalt carbon fiber to kaolin is 2:1).

[0053] Among them, the preparation method of asphalt carbon fiber-kaolin is as follows: after drying the kaolin, soak it in 1~2mol / L sodium hydroxide solution for 24~36h, filter, wash to neutrality, and dry to obtain pretreated kaolin; dissolve the asphalt in trichloroethylene, stir evenly to obtain an asphalt solution, and control the temperature at 40~50℃; slowly add the pretreated kaolin to the asphalt solution, mix and react for 2.5~3.5h; carbonize the reaction product under a nitrogen atmosphere, with a heating rate of 5℃ / min, a final temperature of 600~800℃, and keep warm for 2h; cool to room temperature, grind and sieve 200 mesh, acid wash to remove impurities, wash with water to neutrality, and dry at 60℃.

[0054] The preparation methods of other raw materials and treatment agents are referred to Example 1.

[0055] Example 6

[0056] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 3 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:2), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 5 parts of sodium hydroxide, 12 parts of activated carbon, 6 parts of citric acid, and 5 parts of asphalt carbon fiber-kaolin (the mass ratio of asphalt carbon fiber to kaolin is 2:1). The preparation method of the raw materials and the treatment agent is as in Example 1. The preparation method of the raw materials and the treatment agent is as in Example 5.

[0057] Example 7

[0058] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 3 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:4), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 5 parts of sodium hydroxide, 12 parts of activated carbon, 6 parts of citric acid, and 10 parts of pitch carbon fiber-kaolin (the mass ratio of pitch carbon fiber to kaolin is 1.5:1). The preparation method of the raw materials and the treatment agent is referenced to Example 5.

[0059] Example 8

[0060] The raw materials of the treatment agent for landfill leachate membrane concentrate are: 3 parts of carbon nanotube-gellan gum (the mass ratio of carbon nanotube to gellan gum is 1:4), 20 parts of hydrogen peroxide / persulfate, 10 parts of polyacrylamide, 5 parts of sodium hydroxide, 12 parts of activated carbon, 6 parts of citric acid, and 7.5 parts of pitch carbon fiber-kaolin (the mass ratio of pitch carbon fiber to kaolin is 2.5:1). The preparation method of the raw materials and the treatment agent is referenced to Example 5.

[0061] Comparative Example 1

[0062] Compared with Example 1, the only difference is that the carbon nanotube-gellan gum is replaced by an equal amount of gellan gum.

[0063] Comparative Example 2

[0064] Compared with Example 1, the only difference is that the carbon nanotube-gellan gum is replaced by an equal amount of carbon nanotubes.

[0065] Comparative Example 3

[0066] Compared with Example 1, the only difference is that carbon nanotube-gellan gum is not used.

[0067] Comparative Example 4

[0068] Compared with Example 1, the only difference is that the mass ratio of carbon nanotubes to gellan gum is 1:1.

[0069] Comparative Example 5

[0070] Compared with Example 1, the only difference is that the mass ratio of carbon nanotubes to gellan gum is 1:5.

[0071] Comparative Example 6

[0072] Compared with Example 5, the only difference is that the mass ratio of asphalt carbon fiber to kaolin is 1:1.

[0073] Comparative Example 7

[0074] Compared with Example 5, the only difference is that the mass ratio of asphalt carbon fiber to kaolin is 3:1.

[0075] Test verification:

[0076] 1. Dispersion stability determination

[0077] The landfill leachate membrane concentrate treating agent of each embodiment and comparative example was prepared into a 1 g / L aqueous dispersion, ultrasonically dispersed for 30 minutes, and measured by dynamic light scattering (DLS).

[0078] 2. Organic matter adsorption capacity

[0079] The landfill leachate membrane concentrate treating agent of each embodiment and comparative example was pretreated at 105°C and dried for 24h, 2g / L treating agent was added to the landfill leachate membrane concentrate, the temperature was 25±1°C, the oscillation condition was 150rpm, the contact time was 240min, COD was determined by potassium dichromate method, and the removal rate and adsorption capacity were calculated.

[0080] Among them, the landfill leachate membrane concentrate comes from the leachate produced by the decomposition of garbage in the landfill. After being treated by membrane technology (such as nanofiltration and reverse osmosis), the concentrate has complex components and high concentration of organic pollutants. The COD is 1000~5000mg / L, and can reach up to 15000mg / L. The inorganic salt component is high, and the conductivity is as high as 20000~50000μS / cm. In addition to the conventional Na + , K + In addition, it also contains heavy metal ions such as Pb and Cu.

[0081] 3. Heavy metal adsorption capacity

[0082] The landfill leachate membrane concentrate treating agent of each embodiment and the control group was pretreated at 105°C and dried for 24h, and 2g / L treating agent was added to the landfill leachate membrane concentrate at a temperature of 25±1°C, an oscillation condition of 150rpm, a contact time of 240min, and the metal ion concentration was determined by ICP-MS to calculate the removal rate and adsorption capacity.

[0083] 4. Conductivity test

[0084] The landfill leachate membrane concentrate treating agent of each embodiment and control group was pressed into a φ13 mm disc with a thickness of 1 mm, and the surface was gold-sprayed and tested with a four-probe resistance tester.

[0085] 5. Determination of ion exchange capacity

[0086] (1) Sample Na + Formation: Soak in 0.1mol / L NaCl for 24h, wash with deionized water until neutral, and dry at 60℃;

[0087] (2) Determination steps: Weigh 1.000 g of the landfill leachate membrane concentrate treatment agent of each embodiment and comparative example, add 100 mL of 0.1 mol / L CaCl2 solution, shake for 24 h, and centrifuge;

[0088] (3) Determination method: flame atomic absorption determination, calculation of ion exchange capacity.

[0089] The above test results are shown in Tables 1 to 3.

[0090] Table 1 Dispersion stability test results

[0091] .

[0092] Table 2 Test results of organic matter and heavy metal adsorption capacity

[0093] .

[0094] Table 3 Test results of conductivity and ion exchange capacity

[0095] .

[0096] From the above results, it can be seen that: dispersion stability: the average particle size of Examples 1 to 8 is all in the range of 150 to 175 nm, and the polydispersity index is lower than 0.25, indicating that the carbon nanotube-gellan gum composite material has excellent dispersion stability; organic matter removal: the COD removal rate of the embodiments is between 89.7% and 94.2%, and the adsorption capacity is 238.4 to 252.3 mg / g, which is significantly better than the comparative example; heavy metal removal: the heavy metal removal rate of the embodiments is between 92.3% and 95.6%, and the adsorption capacity is 75.6 to 80.2 mg / g, and the performance is significantly better than the comparative example; conductive performance: the resistivity of the embodiments is all in the range of 0.02 to 0.03Ω·cm, and the conductivity is excellent; ion exchange capacity: the ion exchange capacity of the embodiments is between 1.18 and 1.32 meq / g, which is significantly higher than the comparative example.

[0097] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A landfill leachate membrane concentrate treating agent, characterized in that: The method comprises the following raw materials in parts by weight: 2 to 5 parts of carbon nanotube-gellan gum, 15 to 25 parts of hydrogen peroxide / persulfate, 8 to 12 parts of polyacrylamide, 3 to 6 parts of sodium hydroxide, 10 to 15 parts of activated carbon, 4 to 8 parts of citric acid, and 5 to 10 parts of pitch carbon fiber-kaolin; Wherein, carbon nanotube-gellan gum is a composite obtained by reacting carbon nanotube and gellan gum in a mass ratio of 1:(2-4); Hydrogen peroxide / persulfate is a composite system of hydrogen peroxide and persulfate.

2. A landfill leachate membrane concentrate treating agent as claimed in claim 1, characterized in that: The persulfate includes any one or more of sodium persulfate, potassium persulfate and ammonium persulfate.

3. The landfill leachate membrane concentrate treating agent according to claim 1, characterized in that: The preparation method of the carbon nanotube-gellan gum is as follows: The pretreated multi-walled carbon nanotubes are uniformly dispersed in deionized water, and a gellan gum solution with a pH of 7 to 8 is added. After sufficient reaction, the mixture is centrifuged, the precipitate is retained, washed, dried, ground and sieved.

4. A landfill leachate membrane concentrate treating agent as claimed in claim 3, characterized in that: The pretreatment of multi-walled carbon nanotubes is to remove impurities and improve dispersion.

5. The landfill leachate membrane concentrate treating agent according to claim 1, characterized in that: The pitch carbon fiber-kaolin is a composite obtained by reacting the pitch carbon fiber and kaolin in a mass ratio of (1.5-2.5):

1.

6. The landfill leachate membrane concentrate treating agent according to claim 1, characterized in that: The preparation method of asphalt carbon fiber-kaolin is as follows: the pretreated kaolin is evenly mixed with the asphalt solution, carbonized at high temperature under a nitrogen atmosphere, and then cooled, ground, sieved, washed and dried.

7. The landfill leachate membrane concentrate treating agent according to claim 6, characterized in that: The pretreatment of kaolin is to remove impurities and change the surface chemical properties of kaolin.

8. The landfill leachate membrane concentrate treating agent according to claim 6, characterized in that: The carbonization temperature is 600~800℃.

Citation Information

Patent Citations

  • Method and process for advanced treatment of well drilling effluent

    CN102139971A

  • Large-scale single-walled carbon nanotube purification method based on supramolecular functionalization

    CN102153071A

  • Composite water treatment agent, preparation method and application thereof

    CN110467251A